The proteome of developing barley anthers during meiotic prophase I. (10th November 2021) - Lewandowska, Dominika; Orr, Jamie; Schreiber, Miriam; Colas, Isabelle; Ramsay, Luke; Zhang, Runxuan; Waugh, Robbie
Abstract: Flowering plants reproduce sexually by combining a haploid male and female gametophyte during fertilization. Male gametophytes are localized in the anthers, each containing reproductive (meiocyte) and non-reproductive tissue necessary for anther development and maturation. Meiosis, where chromosomes pair and exchange their genetic material during a process called recombination, is one of the most important and sensitive stages in breeding, ensuring genetic diversity. Most anther development studies have focused on transcript variation, but very few have been correlated with protein abundance. Taking advantage of a recently published barley anther transcriptomic (BAnTr) dataset and a newly developed sensitive mass spectrometry-based approach to analyse the barley anther proteome, we conducted high-resolution mass spectrometry analysis of barley anthers, collected at six time points and representing their development from pre-meiosis to metaphase. Each time point was carefully staged using immunocytology, providing a robust and accurate staging mirroring our previous BAnTr dataset. We identified >6100 non-redundant proteins including 82 known and putative meiotic proteins. Although the protein abundance was relatively stable throughout prophase I, we were able to quantify the dynamic variation of 336 proteins. We present the first quantitative comparative proteomics study of barley anther development during meiotic prophase I when the important process of homologous recombination is taking place. Abstract : We performed a comprehensive proteomics study of accurately staged developing early meiotic anther in barley, providing new insight into the development of the male reproductive organ in small grain cereals.